PENINGKATAN PRODUKTIVITAS ALAT MUAT SEKELAS OHT CAT 777 DI PERTAMBANGAN BATUBARA DENGAN PENDEKATAN QUALITY CONTROL CIRCLE - Arif Nuryono; Didin Sjarifudin; Qadhi Ahmad (JURNAL TEKNIK INDUSTRI, 2016)
PT Riung Mitra Lestari trying to improve the main load tool off high way truck (OHT) from one of theirjob site dari salah satu job site owned PT. RML, Job Site Krassi, North Kalimantan where data showedgains in productivity tools primarily under standard load. In January – August 2015 trend ofproductivity gains is 83%. Krassi site that has the most difficult locations and conditions of 80% peatland. With the location With a location 80% peat into one unique in handling dan its mining methods.Research conducted using the QCC method to improved productivity mining equipment. Improvementgroup is often called QCC uses severeal tools improvement and productivity improvement measures.Inthe analysis of the probem or step 3 there are several causes at the root of the problem of inaccesibilityCat hauler unit 777. In actual achievement prior to productivity improvement tool hauler Cat 777 is 78bcm / hour of a target of 100 bcm / hour.In percentage only reaches 78% and the target after QCCapplication is expected to reach 95%. Based on fishbone and pareto analysis major problem and thedominant causes of the failure in the productivity tool loading and unloading is less good technique,the second is the lack of a hard material that serves as mixing and blending. By making improvementin loading technique and road repair there is productivity improvement 57,3 % dari from previous dataand 22,8 % improvement from target. The other factor that affected incapability of production is losstime. After QCC improvement loss time decreased into 90,14 minutes per days from previously 227,14minutes / days.